Antenatal detection of grossly distended bladder owing to absence of the urethra in a fetus with trisomy 18. Issue 2 (April 1983) - Nevin, N C; Nevin, J; Dunlop, J M; Gray, M
Abstract : An ultrasonic examination revealed a grossly distended fetal abdomen. Amniocentesis at 19 weeks' gestation showed raised amniotic fluid alphafetoprotein, a second band of specific acetylcholinesterase, and a fetal karyotype 47, XY, +18. The pregnancy was terminated and the necropsy examination showed absence of the urethra, grossly distended bladder, hydroureters, and congenital heart anomalies.